Tatiana Omrina tells several stories - Tatiana Omrina (Alexander King, 1998)
Omrina tells several stories to Tatiana Yatylkut (sitting to right off frame) and King (depositor) in her home. Some others may have been present, too. Speaker is blind since early childhood.